(untitled) (SCHOOLAR: Social and Literature Study in Education, 2023)
This study aims to develop an interactive learning media called Gerhana (Gerakan Pembaruan Islam Indonesia) for SKI subject in the form of an android application. This media is used to determine product feasibility and studentsâ€™ perspective responses to Gerhana media application. Quantitative research was conducted in this study. Research instruments for students are used to determine learning objectives, quality of material content, motivation, design, and use on media made by researchers. This instrument was given to XI MAN 9 JOMBANG class students as many as 30 students. student response questionnaires were analyzed quantitatively, then described or conclusions were drawn. Analyze the assessment of students using the Likert scale method. The results of this study were seen from the student response questionnaires with an average score of 80% with feasible criteria. Thus, it can be seen from the results of the user test that the student’s perspective to the Gerhana media application (Gerakan Pembaruan Islam Indonesia) is feasible to use. This media can be used by teachers as a variety of learning media and hopefully can be applied in other subjects so that it can help practicality in the learning process. This research is able to facilitate students in the learning process by using Gerhana application as a media. Future researchers are expected to refine application-based learning media, because there are still many things that can be developed in application-based learning media.